HotFill: A cooling time constrained raster-fill planning algorithm for extrusion 3D printing. (November 2022) - Nakonetchnei, Elis C.; Stolfi, Jorge; Volpato, Neri; da Silva, Ricardo D.; Minetto, Rodrigo
Abstract: One of the factors responsible for the mechanical strength of objects manufactured by thermoplastic extrusion 3D printers is the adhesion between adjacent material beads in the same layer. This, in turn, depends on the time lapsed between their deposition. In this paper we describe HotFill, an algorithm that finds a tool-path for solid raster infill that keeps the cooling time intervals between depositions below user-specified limits. The algorithm, based on the dynamic programming technique, was implemented in Python and tested on several representative slices of 3D models. The results show that HotFill is fast and produces tool-paths that have low fabrication time while respecting the cooling time constraints. The source code and datasets are available at GitHub. Highlights: Strength of a 3D printed part depends on good bonding between infill rasters. Bond strength depends on time lapsed between deposition of adjacent rasters. Problem: build a tool-path with prescribed limits for inter-raster cooling times. A practical dynamic programming algorithm for time-constrained tool-path generation is proposed. The algorithm is tested on some representative part slices.